Financial and other indicators for measurement of the regional disparities in Slovakia in 2005 - 2015 - Peter Pisár; Martin Varga (European Financial and Accounting Journal, 2017)
The decentralization of lower-level government and the formation of self-governing regions NUTS III in SR are also accompanied by the formation of regional differences in the form of disparities. They are one of the basic problems not only at the level of Slovakia but also at European regions level. The European Union, in co-operation with national strategies, regularly develops documents and strategies to eliminate regional disparities across countries. The aim of the paper is to evaluate the selected quantitative approaches for measuring regional differences in the municipalities at the level of NUTS III in Slovakia from the point of view of selected indicators at different levels of their survey - micro, macro and non-economic. To measure the size and development of regional differences, selected mathematical and statistical methods will be used, and then the results obtained by using the comparison method will be summarized. Using selected methods, we have confirmed that disparities prevail among the regions at all levels of their exploration, from macroeconomic to noneconomic. We have pointed out that regional disparities can not be alleviated, even in some cases we note some enlarging of those disparities. Such a development should lead to a review of the further development of SR regional policy and public policies.
Keywords: R58; 650; Disparities; Indicators; Regions